Research on secret key generation based on wireless channel characteristics in body area network - Jingjing HUANG (Dianxin kexue)
Wireless body area network (WBAN) is a human-centered wireless network.With limitations of power and computation capabilities of WBAN, the significant challenge of ensuring security is how to generate a shared key between two entities based on a lightweight symmetric cryptography.To investigate this issue, a secret key generation scheme in ultra-wideband (UWB) WBAN was designed.In this scheme, the difference of multipath relative delay and its average value were chosen as common random source to reduce key mismatch probability.Furthermore, with the aid of relay, secret key generation rate could be increased.Simulation and test results demonstrate that the proposed scheme can achieve a good tradeoff between key match probability and key generation rate.Furthermore, security analysis of the scheme was also provided to validate its feasibility.